Study protocol of a German multi-center, observer-blind, randomized, and actively controlled parallel-group trial comparing maintenance electroconvulsive therapy to treatment as usual for relapse prevention in clozapine resistant schizophrenia - Deicher, Anton; Karl, Sebastian; Otte, Marie-Luise; Knabbe, Johannes; Wendel, Bernadette; Gose, Maria; Wolf, Robert Christian; Sartorius, Alexander (BMC psychiatry, 2025)
Schizophrenia is one of the most severe and costly mental disorders in terms of human suffering and societal expenditure. About 15-30% of patients do not respond to all known antipsychotics, including clozapine, the current gold standard in these cases. Electroconvulsive therapy (ECT) is well-known to be highly effective in clozapine-treatment-resistant schizophrenia (CRS), and synergistic effects of clozapine and ECT have been demonstrated. However, relapse rates after successful courses of ECT are still very high, and evidence for maintenance ECT (mECT) in CRS is scarce at best.